Earnings management and Corporate Tax Planning and their impacts on Firm Value / Nik Mohd Norfadzilah Nik Mohd Rashid - Mohd Rashid, Nik Mohd Norfadzilah Nik (2017)
The research aimed to study the impacts of Earnings Management (EM) and Corporate Tax Planing (TP) on the changes of the Firm Value (FV) among public listed companies in Malaysia. Financial determinants of EM and Corporate TP which were both creative accounting strategies that formed the predictor variables, had first been identified. These were obtained from secondary data of 357 selected public listed companies from 2001 until 2012 retrieved from Thompson One Data stream database. Diagnostic analyses were performed to test normality and serial correlation of the data and obtain descriptive statistics including the analysis of variance for both EM and TP among the companies in the selected industries. Hence, in this study the measurement used for EM was related to the Accrual Earnings Management (AEM) and Real Earnings Management (REM) while the measurement for TP referred to accrual-based Effective Tax Rates (ETR1) and cash-based Effective Tax Rate (ETR2) level of the companies. Balance panel data of the selected companies within 12-year period produced 4,284 firm-year observation for further analyses determined by specification methods comprising Pooled Ordinary Least Squares, Fixed Effect and Random Effect regression analyses. The investigation were continued for the first phase of the study which related to the investigation of the financial determinants towards EM and Corporate TP among the companies. Results from the first phase initially disclosed that there was a significant relationship that existed between the selected financial transactions towards the EM and TP in the business transaction activities. In the second and third phases, the relationship between EM and changes in FV as well as the relationship between TP and changes inFV in the companies were analysed respectively. The findings revealed that there were significant relationships that existed between EM and the changes in FV as well as between TP and changes in FV. Hence, it can be concluded that both EM and TP creative accounting strategies were important to be used by the companies in order to stimulate changes in FV transactions in the business transaction activities. In the fourth phase, indirect effects of selected financial attributes of EM and Corporate TP on the changes in FV were examined. The findings provided empirical evidence of the existence of the influence of Audit Quality (AQ), Deferred Tax (DTX), Government Ownership Percentage (GOP) and Financial Distress (FDR) to be significantly meaningful on the relationship between AEM strategies and the changes in FV as well as on the relationship between ETRs and the changes in FV. Results showed that there were partial mediation effects of the financial attributes in the relationships of EM and TP, which were measured by AEM strategies and ETR1 respectively, on FV. Finally, in the fifth phase, indirect effects of the Corporate TP on the relationship between EM and changes in the Firm Value were examined. The findings also revealed that Corporate TP was found to be partially significant in mediating the relationship between EM strategies and changes in the Firm Value in the companies. Overall, it can be concluded that both EM and Corporate TP were important creative accounting strategies that should be mutually studied because they had significant influence on the changes of the Firm Value in the companies. Therefore, the current study provided evidence regarding the usefulness of the information from EM and Corporate TP in the business transaction activities.